Diversidade de besouros escolitíneos (Coleoptera: Scolytinae) em remanescentes urbanos de floresta de araucária e sua relação com características fitossociológicas - Santos, Adriana da Silva (2023)
As urban growth progresses, the degradation of natural ecosystems reduces the resilience of cities. Considering the process of anthropisation to which urban forest remnants have been subjected, insects can be essential bioindicators of changes in the environment resulting from anthropogenic disturbances or natural stressors. Among the saproxylic insects, the beetles of the subfamily Scolytinae (Coleoptera: Curculionidae) have been identified as bioindicators of the environmental quality of forest remnants and forest stands. Thus, given the importance of urban forest remnants in providing ecosystem services and considering the scarcity of information on the saproxylic entomofauna in these environments, we investigated the relationships between the forest structure of four Araucaria Forest remnants present in Curitiba-PR Municipal Parks and the diversity of beetles of the Scolytinae subfamily, seeking to detect potential indicator species of the environmental balance of the remnants. The research consisted of the following stages: (1) collection of coleopteran samples using ethanolic traps; (2) analysis of Scolytinae community descriptors; (3) phytosociological characterisation of forest remnants in urban parks; (4) analysis of the relationship between the phytosociological characteristics of forest remnants and the structure of the Scolytinae community; (5) analysis of the population fluctuation of the most representative Scolytinae species, in contrast to meteorological factors; (6) verification of the bioindication potential of the Scolytinae species sampled. Sixty-one species of Scolytinae were identified, with the genus Corthylus predominating. The most excellent richness and diversity of beetle species, as well as the most remarkable faunal similarity, were observed in the parks with the most minor forest remnants (Parque Natural Municipal de Lazer “General Iberê de Mattos” and Parque Municipal da Barreirinha). At the same time, the most significant abundances were recorded in the largest remnants (Parque Natural Municipal Barigui and Zoológico Municipal). Of the species sampled, 14 were considered potential indicators, of which two were classified as characteristic (Corthylus sp01 and Tricolus sp01) and the others as detectors (Microcorthylus quadridens, Monarthrum quadridens, Microcorthylus minimus, Xyleborus affinis, Monarthrum sp01, Corthylus sp03, Corthylus sp10, Corthylus sp04, Corthylus sp15, Corthylus nigrencens, Xyleborinus gracilis, Corthylus sp08). The abundance and richness of scoliotes varied between seasons, with population peaks being observed in the summer of 2018/2019 and winter of 2020. It was found that the absolute density and basal area of standing dead trees were the phytosociological characteristics with the most significant influence on the structure of the beetle community. However, the floristic composition also had a significant influence.